Estimativa da evapotranspiração real em área de relevo acidentado utilizando o SEBAL - Andre Luiz Profeta (2017)
Evapotranspiration is one of the processes that redistributes water and energy in the Earth system. This is an essential variable for hydrological and climate models, which contributes for the sound management of water resources in the local, regional and global scales, as well as in natural (watersheds and biomes) or artificiais systems (agriculture and pasture lands). This study aims at estimating the daily and hourly real evapotranspiration in a mountain terrain using the Surface Energy Balance Algorithms for Land (SEBAL), Landsat 8 imagery and meteorological data. Two models were made in the area of the Piranga River Water Resources Management Unit (UPGRH DO1): firstly, without considering the influence of the relief (Model 1); secondly, considering it (Model 2). Applying SEBAL, the latent heat flux () is estimated as a residual of the simplified energy balance equation. From the , which corresponds to the energy used in the evapotranspiration process, the hourly real evapotranspiration is calculated. Then, using the evaporative fraction, the daily real evapotranspiration is calculated. The results show the evapotranspiration spatial variability and the different land cover in the area water vapor contribution to the atmosphere. Comparing the results with the reference evapotranspiration (0) calculated by the FAO Penman-Monteith equation and the crop evapotranspiration () from the Eucalyptus plantation, the results of the two models were consistent. Also, the results from the second model tend to be below the results of the first model. In both models, the effect of vegetation in the energy flux across the surface is evident.